Application of the SAW Method in the Decision Support System for Employee Performance Assessment at PT. Sarma Amarise Anugerah Sejahtera - Naibaho, Eltrina (Jurnal Multimedia dan Teknologi Informasi (Jatilima), 2024)
Employee performance appraisal is an important aspect of human resource management, but it often faces challenges related to subjectivity and inaccuracies. PT. Sarma Amarise Anugerah Sejahtera faces this problem in its manual and less objective performance assessment system. This study aims to design and implement a decision support system based on the Simple Additive Weighting (SAW) method to improve objectivity, efficiency, and accuracy in employee performance assessment. The SAW method is used to evaluate performance based on various criteria, by giving weight to each relevant criterion. The results of this system are expected to provide more transparent and accountable decisions, as well as assist management in planning the right development and policies for employees. The results of the study show that the application of the SAW method in employee performance assessment at PT. Sarma Amarise Anugerah Sejahtera can improve the quality of decision-making and minimize the bias that usually appears in manual assessment systems.